Caught in the Loop: Examining the Link Between Alexithymia and TikTok Addiction Among Adolescents in Jakarta - Aqilah, Najwa Salma; Trihandayani, Dewi (Universitas Negeri Malang, 2024)
This research explores the relationship between alexithymia tendencies and TikTok addiction among adolescents in Jakarta. A total of 300 adolescents aged 18–24 who use TikTok for at least three hours per day participated in this quantitative research. Data were collected using the Toronto Alexithymia Scale (TAS-20) and the Social Media Addiction Scale-Short Form (SMAS-SF) to measure levels of alexithymia tendencies and TikTok addiction. Data analysis used bivariate correlation or Pearson’s correlation coefficient by SPSS for Windows 26 to assess the relationship between the two variables. Results from two-tailed testing with a significance level of .01 (1%) revealed a positive correlation of .299. These findings indicate that higher levels of alexithymia are associated with higher levels of TikTok addiction.